Teachers, discourses, and authority in the postmodern composition classroom - Gale, Xin Liu, 1952- (State University of New York Press, 1996)
Annotation Drawing on the ideas of the major poststructuralists, Gale (rhetoric and writing, U. of Arkansas-Little Rock) investigates the teacher's role and authority in postmodern academic settings. She untangles the complex relationships among the teacher's and the institution's authority, the teacher's discourse and social and pedagogic roles, and students' discourses and diverse backgrounds. She proposes a two-level interactional model of teaching based on an edifying role for the teacher. Annotation copyright by Book News, Inc., Portland, OR.
Keywords: English language -- Rhetoric -- Study and teaching.; English language -- Discourse analysis.; Report writing -- Study and teaching.; English teachers -- Training of.; Postmodernism.; Authority.; Rapports -- Rédaction -- Étude et enseignement.; Postmodernisme.; Autorité.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; REFERENCE -- Writing Skills.; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing.; Authority; English language -- Discourse analysis; English language -- Rhetoric -- Study and teaching; English teachers -- Training of; Postmodernism; Report writing -- Study and teaching; English Language.; English.; Languages & Literatures.